The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1309/ajcpjf1yufg6gtfi
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Pathology and Laboratory Errors

Abstract: Physicians are urged to communicate more openly following medical errors, but little is known about pathologists' attitudes about reporting errors to their institution and disclosing them to patients. We undertook a survey to characterize pathologists' and laboratory medical directors' attitudes and experience regarding the communication of errors with hospitals, treating physicians, and affected patients. We invited 260 practicing pathologists and 81 academic hospital laboratory medical directors to participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, there were differences in the intention to conduct DPSI according to the type of medical error, similarly to what was observed with regard to actual frequency and intentions in hypothetical cases. In particular, most medical professionals still thought that DPSI was unnecessary in the case of a near miss [17,22,28-32]. For example, Evans et al [30] reported that 71.6% of radiation oncologists and trainees thought that near misses should not be disclosed, although 94.8% of them thought that serious medical errors should be disclosed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there were differences in the intention to conduct DPSI according to the type of medical error, similarly to what was observed with regard to actual frequency and intentions in hypothetical cases. In particular, most medical professionals still thought that DPSI was unnecessary in the case of a near miss [17,22,28-32]. For example, Evans et al [30] reported that 71.6% of radiation oncologists and trainees thought that near misses should not be disclosed, although 94.8% of them thought that serious medical errors should be disclosed.…”
Section: Resultsmentioning
confidence: 99%
“…According to the article by Evans et al [30], 38.0% of radiation oncologists and trainees thought that DPSI increased the likelihood of being sued, although 32.4% felt that DPSI decreased the likelihood of being sued. However, according to the study of Dintzis et al [28], only 11.2% of anatomic pathologists and laboratory medical directors thought that fear of being sued would influence their recommendations regarding DPSI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations